The influence of propofol-based total intravenous anesthesia on postoperative outcomes in end-stage renal disease patients: A retrospective observation study. - Ho Bum Cho; Mun Gyu Kim; Sun Young Park; Sanghoon Song; Youn Sil Jang; Suyeon Park; Hyun Keun Lee; Jae Hwa Yoo; Ji Won Chung; Sang Ho Kim (PLoS ONE, 2021)
Background To determine whether the anesthetic method of propofol total intravenous anesthesia (TIVA) is associated with postoperative outcome in ESRD patients, we evaluated the incidence of postoperative major adverse cardiac events (MACE), comparing propofol TIVA versus anesthesia with volatile anesthesia in ESRD patients. Methods Retrospectively, we identified cases with ESRD patients who underwent surgery under general anesthesia. Patients were divided into those who received only volatile anesthesia (volatile group) and those who received only propofol TIVA (TIVA group). The incidence of MACE and potential confounding variables were compared separately in a univariate logistic model and subsequently by multivariate logistic regression. Results Among the 2576 cases in ESRD patients, 1374 were in the TIVA group and 1202 were in the volatile group. The multivariate analysis included 12 factors, including the anesthesia method, of which five factors were significant. Factors that were associated with a significantly lower MACE risk included preoperative chloride concentration (OR: 0.96; 95% CI, 0.92-0.99), baseline SBP (OR: 0.98; 95% CI, 0.98-0.99), and propofol TIVA (OR: 0.37; 95% CI, 0.22-0.60). Conclusions We inferred that the anesthetic method associated with the postoperative outcome in patients with ESRD.